ANALYSIS OF ENTREPRENEURSHIP AND ENTREPRENEURIAL INTENTION AMONG YOUNG MINAHASA WOMEN IN MANADO - Darungo, Andrew; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The development of entrepreneurship in Manado effected the opportunity of entrepreneurship in Manado is opened. The advantage of business opportunity in Manado should been utilized by all people in Manado young Minahasa women to run a business. But, the entrepreneurial intention of young Minahasa women in Manado is questionable. The objective of this research is to analyze the intention to become entrepreneur among young Minahasa women in Manado, and their view about women entrepreneurship in Manado. This research used qualitative methods, by conducting interviews to figure out the entrepreneurial intention of young Minahasa women in Manado. The population includes young women from Minahasa ethnicity, aged 19-23 years old. The informant of this research is 9 young Minahasa women, mostly university students. The result showed that young Minahasa women in Manado have intention to become entrepreneur and have positive opinion about entrepreneurship in Manado. Entrepreneurial intention of young women is need to improve by training, socialization, or entrepreneurship education in university. Keywords: entrepreneurship, entrepreneurial intention, women entrepreneurship